2004
DOI: 10.1128/aem.70.12.7497-7510.2004
|View full text |Cite
|
Sign up to set email alerts
|

Complete Nucleotide Sequence of the Conjugative Tetracycline Resistance Plasmid pFBAOT6, a Member of a Group of IncU Plasmids with Global Ubiquity

Abstract: This study presents the first complete sequence of an IncU plasmid, pFBAOT6. This plasmid was originally isolated from a strain of Aeromonas caviae from hospital effluent (Westmorland General Hospital, Kendal, United Kingdom) in September 1997 (G. Rhodes, G. Huys, J. Swings, P. McGann, M. Hiney, P. Smith, and R. W. Pickup, Appl. Environ. Microbiol. 66:3883-3890, 2000) and belongs to a group of related plasmids with global ubiquity. pFBAOT6 is 84,748 bp long and has 94 predicted coding sequences, only 12 of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 60 publications
(77 reference statements)
2
76
1
Order By: Relevance
“…In addition, our study demonstrated that this IncU-type plasmid-mediated qnrS2 gene was expressed and able to confer reduced susceptibility to quinolones, at least in E. coli. Aeromonas species and IncU plasmids, which are ubiquitous in a wide range of environments, might therefore act as important vectors for transfer of plasmid-mediated quinolone resistance determinants (23). As opposed to most qnrA and qnrB genes, qnrS genes have never been reported to be associated with sul1-type class 1 integrons (6,8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our study demonstrated that this IncU-type plasmid-mediated qnrS2 gene was expressed and able to confer reduced susceptibility to quinolones, at least in E. coli. Aeromonas species and IncU plasmids, which are ubiquitous in a wide range of environments, might therefore act as important vectors for transfer of plasmid-mediated quinolone resistance determinants (23). As opposed to most qnrA and qnrB genes, qnrS genes have never been reported to be associated with sul1-type class 1 integrons (6,8).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cloning of EcoRI-restricted DNA from whole-cell DNA of A. media 42 showed that the qnrS2 gene was inserted into the mpR gene in plasmid p42. No tetA gene encoding resistance to tetracycline was detected by PCR in plasmids p37 and p42, whereas it was identifi ed in plasmid pFBAOT6 (23).…”
Section: Qnrs2 Gene On Incu-plasmid Backbonementioning
confidence: 99%
See 1 more Smart Citation
“…The flanking region by IS26-Left and -Right was identical to the structure found in Photobacterium damselae Kim et al, 2008;Kim and Aoki, 1994 except for the ISRSB101. The inserted ISRSB101 was 100% identical to that of plasmid pFBOAT6 of Aeromonas punctata Rhodes et al, 2004 , and was bordered by direct repeats of 9 nucleotide 5 -TGTTGCAAA-3 originating from IS26-Inner. By nucleotide sequencing of PCR-amplified products, we confirmed the presence of the same structures in Citrobacter sp.…”
Section: Is26-innermentioning
confidence: 99%
“…TA3 pTCKM3 . Solid bars indicate the regions which exhibit homology to the reported sequences; pP99-018 from Photobacterium damselae Kim et al, 2008;Kim and Aoki, 1994 , Salmonella serovar Ordnez Allard et al, 1993 , and pFBAOT6 from Aeromonas punctata Rhodes et al, 2004 . B The structure found in Salmonella sp.…”
Section: Figmentioning
confidence: 99%